EVALUATION OF ANALGESIC, CYTOTOXIC AND ANTIOXIDANT ACTIVITIES OF BLUMEA MEMBRANACEA DC - JIMUTY ROY; MD. RUHUL KUDDUS; BILKIS BEGUM; CHOUDHURY M. HASAN (International Journal of Pharma and Bio Sciences, 2012)
In the present study, the crude methanolic extract of whole plant part of Blumea membranacea (Asteraceae) and its fractions obtained by Kupchan method were screened for their possible analgesic, cytotoxic and antioxidant activities. The analgesic activity of the samples was evaluated using acetic acid induced writhing method in Swiss-albino mice. In this method, acetic acid is administered intraperitoneally to the experimental animals to create pain sensation. As a positive control, diclofenac sodium was used to serve the purpose. The cytotoxic activity was evaluated by brine shrimp lethality bioassay while antioxidant effect was measured by 1,1-diphenyl-2-picrylhydrazyl-hydrate (DPPH) free radical scavenging assay. The crude extract and it’s all Kupchan fractions were found to have significant (p<0.001) analgesic activity at the oral dose of 100 mg/kg body weight. The ethyl acetate soluble fraction of crude methanolic extract demonstrated significant analgesic activity with writhing inhibition of 59.17% compared to 66.66% exhibited by standard diclofenac sodium. In brine shrimp lethality bioassay, the petroleum-ether soluble fraction exhibited maximum toxicity towards the shrimp with LC50 value of 0.841 μg/ml. In case of antioxidant screening, all the partitionates revealed mild to moderate free radical scavenging activity.